Adaptive Learning Organizations (ALOs) Madrasah Aliyah Sistem Ma’had (Islamic Boarding School) - Wasila, Faizatul; Arifin, Imron; Maisyaroh (TAWAZUN: Jurnal Pendidikan Islam, 2024)
This research aims to explore the Adaptive Learning Organization (ALOs) implemented in the Madrasah system Ma'had (Islamic Boarding School) studied at MA Salsabila Islamic Boarding School. Madrasah is an Islamic educational institution which is known for its success in forming the religious character of students, especially a madrasah which has a Ma'had or Islamic Boarding School (IBS) which is increasingly in demand by the community. To maintain the existence of change so that it remains superior and a reference, there needs to be an adaptive strategy to form a good Learning Organization. The research method used is descriptive qualitative, with data collection techniques using interviews, documentation and observation. The results of this research state that ALOs begin by analyzing internal and external changes in madrasas, by expanding the scope of cooperation (networking) as well as selecting and sorting the entire process, making madrasas distinctive (distinctive) and also reflected in the teaching and learning process between educators and students in Madrasah. Abstrak Penelitian ini bertujuan untuk menggali terkait Adaptive Learning Organization (ALOs) yang diterapkan di madrasah sistem Ma’had (Islamic Boarding School) studi di MA Salsabila Islamic Boarding School. Madrasah merupakan Lembaga Pendidikan Islam yang dikenal dengan keberhasilannya dalam membentuk karakter siswa yang religius, terlebih lagi suatu madrasah yang memiliki Ma’had atau Islamic Boarding School (IBS) yang kian diminati oleh masyarakat. Untuk menjaga eksistensi dari perubahan supaya tetap unggul dan rujukan perlu adanya strategi adaptif guna membentuk Learning Organization yang baik. Metode penelitian yang digunakan adalah deskriptif kualitatif, dengan teknik pengumpulan data menggunakan wawancara, dokumentasi dan observasi. Hasil dari penelitian ini menyatakan bahwa ALOs diawali dengan menganalisis perubahan internal dan eksternal madrasah, dengan perluasan cakupan kerja sama (networking) serta pemilihan dan pemilahan keseluruhan proses, membuat madrasah menjadi khas (distingtif) dan juga tergambar dalam proses belajar mengajar antara pendidik dan santri di Madrasah.